Biological activity and applications of natural compounds - Seca, Ana M. L. (2020)
Nature represents an amazing source of inspiration since it produces a great diversity of natural compounds selected by evolution, which exhibit multiple biological activities and applications. A large and very active research field is dedicated to identifying biosynthesized compounds, to improve/develop new methodologies to produce/reuse natural compounds and to assess their potential for pharmaceutical, cosmetic and food industries, among others, and also to understand their mechanism of action.